Diosmin Alleviates Venous Injury and Muscle Damage in a Mouse Model of Iliac Vein Stenosis - Guo, Zhiye; Du, Xiaolong; Zhang, Yihua; Su, Chunwan; Ran, Feng; Lu, Qiulun (Frontiers in Cardiovascular Medicine, 2022)
Iliac vein stenosis (IVS) occurs commonly in affluent countries and are a socioeconomic burden. However, the mechanism underlying venous pathophysiology remains unclear. Mouse model of iliac vein stenosis was generated by iliac ligature, and then treated with micronized diosmin. In this pathophysiological condition, venous permeability is increased, with the elevated levels of inflammatory response and impaired surrounding muscles. Micronized diosmin was in a dose-dependent way to repress the inflammatory stress and maintain the venous integrity. These results indicate that micronized diosmin is an effective therapeutic drug for venous permeability and surrounding tissues.